The PEARSON CORRELATION ANALYSIS OF PRODUCTION COSTS ON THE LAND AREA OF SALT FARMERS IN BOLO SUB-DISTRICT, BIMA DISTRICT - Anna Apriana Hidayanti; Eka Nurminda Dewi Mandalika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Salt is broadly divided into 3 (three) groups, namely salt for human consumption, salt for salting and various foods and, salt for industry. In Indonesia, salt is widely produced by evaporating seawater on a piece of coastal land with the help of wind and sunlight as a source of evaporation energy. The situation above is supported by the condition of the waters of Indonesia, one of which is Bolo District, Sanolo village ranks first in terms of salt production in Bima Regency so that many residents work as salt farmers, production costs in salt farmers in Bolo kecamata include elements of labor wages, depreciation costs of production equipment such as (pump machines, crowbars, sacks, windmills) gasoline costs in activating production aids then tax costs per year. Based on the above explanation, the researcher aims to determine the level of closeness of the relationship between variables in the production cost factor terhadapa land area with the Pearson Correlation Test method. There are 60 samples of salt farmers obtained by purposive sampling obtained the results of the Person Correlation Analysis Test results in the table above it is known that labor costs on the land area of salt farmers have a significant value of 0.000. The significant value between labor costs and the area of paddy rice farming land is 0.000 <0.05, so that the significant value is less than 0.05, it can be concluded that Ho is rejected and H1 is accepted, meaning that there is a significant relationship between labor costs and the land area of salt farmers. From the results of the analysis that has been done, it can be concluded that for variable gasoline costs, variable depreciation of tools, land tax costs and labor costs have a unidirectional and significant relationship, and variable tax costs have the highest correlation with the area of land owned by salt farmers, the more land owned by salt farmers in Bolo District, Bima Regency, the higher the cost of gasoline, variable depreciation of tools, land tax costs and labor costs.